2016
DOI: 10.1111/fcp.12180
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle ischemia–reperfusion injury and cyclosporine A in the aging rat

Abstract: Old patients exhibit muscle impairments and increased perioperative risk during vascular surgery procedures. Although aging generally impairs protective mechanisms, data are lacking concerning skeletal muscle in elderly. We tested whether cyclosporine A (CsA), which protects skeletal muscle from ischemia-reperfusion (IR) in young rats, might reduce skeletal muscle mitochondrial dysfunction and oxidative stress in aging rats submitted to hindlimb IR. Wistar rats aged 71-73 weeks were randomized to IR (3 h unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Impairments in mitochondrial respiration were observed in both claudicating and CLTI experimental models. Indeed, significant reduction in mitochondrial complexes I, II and IV activities was found in muscles of rats submitted to hindlimb ischemia-reperfusion compared to contralateral muscles [18][19][20][21]. Similarly, mouse models of CLTI presented decreased activities of the complexes I, III and IV in ischemic muscles compared with controls [22].…”
Section: Experimental Datamentioning
confidence: 95%
“…Impairments in mitochondrial respiration were observed in both claudicating and CLTI experimental models. Indeed, significant reduction in mitochondrial complexes I, II and IV activities was found in muscles of rats submitted to hindlimb ischemia-reperfusion compared to contralateral muscles [18][19][20][21]. Similarly, mouse models of CLTI presented decreased activities of the complexes I, III and IV in ischemic muscles compared with controls [22].…”
Section: Experimental Datamentioning
confidence: 95%
“…Aging greatly attenuates IRPC (Boengler et al ., ; Fernandez‐Sanz et al ., ). Similarly, cyclosporine A protects from ischemia–reperfusion damage in the young but not in the old (Liu et al ., ; Pottecher et al ., ). It was suggested that the deacetylation of CypD by sirt3 is an important contributor to IRPC (Bochaton et al ., ) and this protection is lost in aged cells because of NAD + depletion, as discussed above.…”
Section: Preconditioning In Ischemia–reperfusion (Irpc) Is Greatly DImentioning
confidence: 97%
“…In the past decade, several in vitro and in vivo studies have confirmed the involvement of MPT in ischemia/RI [83]. The administration of CsA (as well as its analog FK506) has been shown to protect against ischemia/RI in multiple animal models and in multiple tissues, including cardiac and skeletal muscle, brain, kidney, liver, lungs, and testis [84][85][86][87][88][89]. Ppif -KO mice are significantly protected from ischemia/RI in both cardiac muscle and the brain, in terms of both tissue function and survival rates [31,32,90].…”
Section: Role Of Mpt In Reperfusion Injurymentioning
confidence: 99%